Kadar Asam Urat Pada Lansia Peserta Senam di Posyandu Lansia - Fransiska Pangalissani (Poltekkes Kemenkes Semarang, 2022)
Process of getting older causes a person to experience physical and mental, spiritual, economic and social changes as well as degeneration of organ function. Age is one of the risk factors for high uric acid. Uric acid is the final product or waste product from purine metabolism, that excess amount in the blood will crystallize. At an advanced age, there will be a decrease in the production of several enzymes and hormones in the body that play a role in the process of removing gout. Exercise such as elderly gymnastic regularly can delay physiological changes that usually occur in a decrease in strength and flexibility, as well as an increased susceptibility to injury. The results are presented in descriptive form which supported by tables to describe uric acid levels and its causative factors in elderly gymnastic participants at the elderly posyandu in Village Timang, Sub District Wonokerto, District Wonogiri. Examination of uric acid levels from 73 respondents were 42 respondents (57.5%) with normal uric acid levels and 31 respondents (42.5%) with uric acid levels above normal. An increase in uric acid levels can be caused by several factors such as age, sex, food intake, physical activity and history.